Examining Deviant Peer Association as a Moderator of the Relationship Between Borderline Personality Disorder Symptoms and Substance Use - Wojciechowski, Thomas W. (Criminal justice review, 2023)
Borderline personality disorder has been identified as a robust risk factor predicting substance use. There is a dearth of research examining how peer ties may condition this relationship. This study hypothesized that deviant peer association would amplify the relationship between Borderline personality disorder (BPD) symptoms and substance use. The Pathways to Desistance data were analyzed. Ordered logistic regression was used to analyze data. Results indicated that elevated levels of BPD symptoms predicted increased substance use frequency. Deviant peer association moderated the effects of BPD symptoms on marijuana use frequency and daily cigarette use. This moderation effect was in the opposite direction hypothesized, indicating that greater levels of deviant peer association dulled the effect on BPD symptoms on substance use. The unexpected effect indicated that youth reporting symptoms may be buffered against the impact of strain by having any peer relationships, even deviant ones.